IMPLEMENTATION OF SUSTAINABLE DEVELOPMENT GOALS IN THE CONTEXT OF THE IMPLEMENTATION OF TOURIST SERVICES IN THE DIGITAL SOCIETY IN UKRAINE - Taraniuk, Leonid; Korsakiene, Renata; Taraniuk, Karina; Kasian, Olena (Socio-economic relations in the digital society, 2023)
This research examines the important relationship between the sustainability of tourism enterprises in the field of digital innovation, principles of sustainability and participation of tourism enterprises in sustainable development with business performance.The main goal of this research is to analyse the compliance of the Sustainable Development Goals in the activities of the entities of the tourism industry of Ukraine in the conditions of the modern digital development of society. The purpose of the study is closely related to the development of effective tools for sustainable development in Ukraine with an emphasis on finding a balance between the policy of sustainable development and the needs of the tourism business. The main results of the study should include the formation of problematic aspects and perspectives of the work of tourism companies in Ukraine at the current stage of the development of the digital society. The problems faced by enterprises in the tourism sector are highlighted and ways of sustainable tourism that can contribute to economic and social development in the conditions of the post-war development of the country's economy are identified. A graph-analytical analysis of the compliance of the Goals of sustainable development in the work of the tourism industry of Ukraine was carried out. Appropriate ways were formed to eliminate problems and form prospects for the development of the country's tourism industry in the conditions of its post-war development. The main conclusions on the topic of this study were formed, which include the importance of a balance between sustainable tourism practices, digital innovations and business needs to achieve the goals of sustainable development in Ukraine.
Keywords: innovation; digitalization; tourism development; business; sustainable development; natural heritage; Sustainable Development Goals (SDGs); efficiency; company; method